An Investigation of foreign language teaching methods and approaches used by spanish language educators - Woodard, Cassandra (My University, 2011)
This qualitative study investigated which methods and approaches instructors of Spanish as a foreign language have found to be most effective in producing student language learning. In order to research most successful methods and approaches, a population of high school Spanish teachers of La Crosse, Wisconsin was examined. Participants involved consisted of four Spanish language educators who teach various levels of learners. Through interview, observation, and survey, data was collected on the teachers? methods and approaches of instruction along with the beliefs underlying their pedagogy. The data was analyzed using a constant comparative analysis in order to identify trends found across the population studied. In all, the study could not prove one method or approach more effective than the other because of a small research population and broad research question. However, information gathered suggested that further attention can be turned to TPRS, as well as use of instruction that implements meaningful learning, fosters motivation, and accounts for learning differences.
Keywords: Second language acquisition.; Spanish language Study and teaching United States.